2009
DOI: 10.1093/ndtplus/sfp057
|View full text |Cite
|
Sign up to set email alerts
|

Blue kidney in a pale patient--a case for a causal association between renal haemosiderosis in paroxysmal nocturnal haemoglobinuria and chronic kidney disease

Abstract: A 50-year-old man presented with pancytopenia and chronic renal impairment. He had evidence of intravascular haemolysis. The direct antiglobulin (Coomb’s) test was negative. Paroxysmal nocturnal haemoglobinuria (PNH) was diagnosed by the Ham acid haemolysis test. There were no other clinical risk factors that could be implicated in chronic kidney disease (CKD). A renal biopsy revealed extensive haemosiderosis affecting proximal tubular cells and associated interstitial fibrosis as well as tubular atrophy. No g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…Renal hemosiderosis was ruled out because the dead animal was not anemic; this was indicated by a lack of pallor. Anemia is a consistent characteristic feature of hemosiderosis [14,[18][19][20][21][22]. Hemochromatosis was excluded due to the lack of liver fibrosis, a gross pathological finding involving the liver that has been consistently reported in cases of hemochromatosis [12,15,[23][24][25][26][27].…”
Section: An Image Of a Left Kidney Showing Dark Blue Discoloration Of...mentioning
confidence: 99%
“…Renal hemosiderosis was ruled out because the dead animal was not anemic; this was indicated by a lack of pallor. Anemia is a consistent characteristic feature of hemosiderosis [14,[18][19][20][21][22]. Hemochromatosis was excluded due to the lack of liver fibrosis, a gross pathological finding involving the liver that has been consistently reported in cases of hemochromatosis [12,15,[23][24][25][26][27].…”
Section: An Image Of a Left Kidney Showing Dark Blue Discoloration Of...mentioning
confidence: 99%
“…Renal hemosiderosis is not only a rare cause of AKI; it can also induce chronic kidney failure [62]. Asim et al [63] reported a case of detailed evidence of CKD progressing over a few years, associated with pancytopenia, in a patient who had no previous admissions for hemolytic crisis or AKI. His only relevant findings at renal biopsy were hemosiderosis, interstitial fibrosis and tubular atrophy, and he was later diagnosed with PNH.…”
Section: Pnh and Renal Tubulopathiesmentioning
confidence: 99%